2020
DOI: 10.23887/jiah.v10i2.25919
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Religiusitas, Integritas, dan Penegakan Peraturan Terhadap Fraud pada Pengelolaan Keuangan Desa

Abstract: The purpose of this study was to find out the effect of religiosity, integrity, and enforcement of regulations toward fraud in village financial management in Buleleng Regency. This study used quantitative approach which was using primary data sources that was obtained through questionnaires and measured with a Likert scale. The functionary village consisting of the Headman, Secretary, and the Head of Finance with the total population of 387 functionary village in Buleleng Regency were chosen as the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
7
0
3
Order By: Relevance
“…Enforcement of regulations is the process of implementing various efforts to implement norms or rules as behavior controls in social life. Fraud as an act that violates the rules needs to be consistently and continuously enforced as well as giving strict sanctions to violators so that fraudulent behavior can be reduced and not repeated (Cahyadi & Sujana, 2020).…”
Section: Regulatory Enforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Enforcement of regulations is the process of implementing various efforts to implement norms or rules as behavior controls in social life. Fraud as an act that violates the rules needs to be consistently and continuously enforced as well as giving strict sanctions to violators so that fraudulent behavior can be reduced and not repeated (Cahyadi & Sujana, 2020).…”
Section: Regulatory Enforcementmentioning
confidence: 99%
“…The results of this study support research conducted by Febriani & Suryandari, (2019) showing that enforcement of regulations has a negative effect on fraud in the government sector. Cahyadi & Sujana, (2020) found that fraud in village financial management is negatively and significantly affected by the variable of enforcement of regulations. Adinda (2015) there is no effect of enforcement of regulations on fraud tendencies.…”
Section: Enforcement Of Regulations On the Fraudulent Tendenciesmentioning
confidence: 99%
“…Hubungan RLG dengan Pengelolaan ADD Tingkat RLG dapat mengontrol perilaku individu dari perilaku yang tidak etis, semakin tinggi tingkat RLG seseorang maka semakin baik dalam melakukan pengelolaan ADD (Giovano et al, 2020). Penelitian mengenai RLG terhadap pengelolaan ADD atau pengelolaan DD sudah pernah dilakukan oleh Cahyadi & Sujana (2020); Giovano, Wibowo, & Yanuarisa (2020); Muhaimin (2021); Hayati & Amalia (2021) yang menemukan bahwa RLG mempunyai pengaruh terhadap pengelolaan ADD atau pengelolaan DD terutama berkaitan dengan kecurangan. Oleh sebab itu, maka dapat dibentuk hipotesis sebagai berikut:…”
Section: Hubungan Kad Dengan Pengelolaan Addunclassified
“…Kemudian hasil penelitian ini didukung oleh penelitian Heriningsih & Sudaryati (2019) yang menyatakan bahwa tingkat RLG tidak dapat memediasi good governance dan kompetensi sumber daya manusia, sehingga tidak berpengaruh terhadap pengelolaan DD. Namun hasil penelitian ini bertolak belakang dengan penelitian yang dilakukan oleh Cahyadi & Sujana (2020); Giovano, Wibowo, & Yanuarisa (2020); Muhaimin (2021); Hayati & Amalia (2021) yang menemukan bahwa RLG berpengaruh terhadap pengelolaan DD terutama berkaitan dengan kecurangan.…”
Section: Pengaruh Rlg Terhadap Pengelolaan Addunclassified
“…Several researches on organizational commitment, human resource competence and spirituality affect the management of village funds such as [3,[12][13][14]. However, other research states that organizational commitment, human resource competence and spirituality do not affect the management of village funds, [15][16]17].…”
Section: Introductionmentioning
confidence: 99%